Ceza muhakemesinde gerekçeli hüküm - Topuz, Fatma Dilan (My University, 2025)
Temel hak ve hürriyetlere en önemli müdahalelerin olduğu hukuk dallarından birini ceza muhakemesi hukuku oluşturur. Bu bakımdan ceza muhakemesi hukukunda gerekçenin varlığı göz ardı edilemeyecek bir etkiye sahiptir. Verilen karar ve hükümlerin gerekçesini öğrenmek, gerek muhakemenin süjeleri gerek denetim mekanizması olan üst derece mahkemeleri gerekse adil bir hukuk devletinde yaşadığı inancında olan toplumdaki bireyler için mühimdir. Bu bakımdan şüpheli/ sanık, mağdur, suçtan zarar gören diğer kişiler, suçun işlendiği toplumdaki bireyler, verilen karar ve hükümleri denetleyecek olan mahkemeler, bu kararlara karşı itiraz etme hak ve yetkisini kullanacak olan Cumhuriyet savcıları ile müdafi ve vekiller verilen kararların gerekçesini öğrenmek isterler ve pek tabii bu hakka sahiptirler. Bununla birlikte ceza yargılamaları bakımından verilen hükümlerin yeterli ve kapsamlı gerekçeyi içermediği herkesçe ifade edilen bir gerçektir. Bu nedenle “ceza muhakemesinde gerekçeli hüküm” konusu, muhakemenin gerekçe açısından en önemli aşaması olan son kararın verilmesi yani hüküm aşaması incelenmek suretiyle ele alınmıştır. Ceza muhakemesinin en önemli maksadı olan maddi gerçeğe ulaşmak gayesinin hasıl olduğu “hüküm” açısından gerekçenin gerekliliği ve önemi yadsınamaz. Çalışmamızda gerekçenin tanımı, tarihi gelişimi, özellikleri, karar ve hükmün ortak özellikleri incelenerek; ulusal ve uluslararası düzenlemelerde karar ve hükümlerde gerekçe gösterilmesi yükümlülüğünün ne şekilde tezahür ettiği ortaya konulmuştur. Bu düzenlemelere ek olarak AİHM ve yüksek mahkemelerin, mahkeme kararlarında gerekçenin nasıl olması gerektiğine ilişkin içtihatlarına yer verilmiştir. Hükmün kendine has özelliklerine ve unsurlarına dair inceleme ve değerlendirmelerden sonra hükümde gerekçe konusu, kısa karar ve gerekçeli karar başlıkları ayrı ayrı olmak üzere ayrıntılı şekilde inceleme konusu yapılmıştır. Ceza Muhakemesi Kanunu’nda düzenlenen hüküm türleri, kanunda aranan şartlar göz önüne alınmak suretiyle, her hüküm çeşidi açısından “olması gereken gerekçenin” özellikleri Yargıtay içtihatları ve yerel mahkeme kararları da dikkate alınarak incelenmiştir. Hükümde bulunması gereken ortak özellikler esasında ceza muhakemesi sürecinde verilen bütün kararlar için de geçerlidir. Ancak gerekçenin bulunması gereken en önemli aşama hükümdür. Bu nedenle kanun koyucu, hükmün gerekçesinin yazılmasını mahkemenin takdirine bırakmamıştır. 5271 sayılı Ceza Muhakemesi Kanunu, hükmün gerekçesini her hüküm türü için tek tek belirtmek suretiyle düzenlemiştir. İnceleme konumuz açısından bu düzenlemeler yol gösterici olmuş ve Kanun’un sistematiğine uyulmak suretiyle hüküm türleri ve bunların hangi gerekçeleri içermesi gerektiği açıklanmaya çalışılmıştır.

Criminal procedure law constitutes one of the most important branches of law that interferes with fundamental rights and freedoms. In this respect, the existence of justification in criminal procedure law has an effect that cannot be ignored. It is important for both the subjects of the proceedings, the courts of higher instance, which are the supervisory mechanisms, and the individuals in the society who believe that they live in a just state of law to learn the justification of the decisions and judgments. In this respect, the suspect/ accused, the victim, other persons harmed by the crime, the individuals in the society where the crime was committed, the courts that will supervise the decisions and judgments, the public prosecutors who will exercise their right and authority to object to these decisions, and the defense attorneys and attorneys want to learn the reasoning of the decisions and of course they have this right However, it is a widely recognized fact that the judgments given in criminal proceedings do not contain sufficient and comprehensive justification. For this reason, the issue of “reasoned judgment in criminal proceedings” is addressed by examining the most important stage of the proceedings in terms of justification, namely the rendering of the final decision, i.e. the judgment stage. The necessity and importance of the justification in terms of “judgment”, where the most important purpose of criminal procedure is to reach the material truth, cannot be denied. In our study, the definition of the justification, its historical development, its characteristics, the common characteristics of the judgment and the verdict are examined, and how the obligation to show justification in judgments and verdicts is manifested in national and international regulations is revealed. In addition to these regulations, the jurisprudence of the ECtHR and the high courts on how the justification should be in court decisions are included. After examining and evaluating the specific features and elements of the judgment, the issue of justification in the judgment has been examined in detail, separately under the titles of short judgment and reasoned judgment. The types of judgments regulated in the Code of Criminal Procedure are examined by taking into account the conditions required by the law, and the characteristics of the “required justification” for each type of judgment are examined by taking into account the jurisprudence of the Court of Cassation and local court decisions. The necessity and importance of the justification in terms of “judgment”, where the most important purpose of criminal procedure is to reach the material truth, cannot be denied. In our study, the definition of the justification, its historical development, its characteristics, the common characteristics of the judgment and the verdict are examined, and how the obligation to show justification in judgments and verdicts is manifested in national and international regulations is revealed. Based on these regulations, the case-law of the ECtHR and the high courts “which examines how the justification should be in the decisions given by the local courts” are included. After the examinations and evaluations on the specific features and elements of the judgment, the issue of justification in the judgment has been examined in detail separately under the titles of short decision and reasoned decision. The types of judgments regulated in the Code of Criminal Procedure are examined by taking into account the conditions sought in the law, and the characteristics of the “justification” for each type of judgment are examined by taking into account the jurisprudence of the Court of Cassation and local court decisions.
Keywords: ceza muhakemesi; Ceza yargılaması; conviction; Criminal procedure; gerekçe; gerekçeli karar; hükümde gerekçe; justification; justification in judgment; Kamu hukuku; mahkûmiyet; Public law; reasoned decision; Turkey; Türkiye